Physical Exercise-Induced Cardiovascular and Thermoregulatory Adjustments Are Impaired in Rats Subjected to Cutaneous Artery Denervation - Malheiros-Lima, Milene R.; Pires, Washington; Fonseca, Ivana A. T.; Joviano-Santos, Julliane V.; Ferreira, Anderson J.; Coimbra, Cândido C.; Lima, Nilo R. V.; Wanner, Samuel P. (Frontiers in Physiology, 2018)
This study aimed to investigate the chronic effects of caudal artery denervation on morphometric parameters of the tail vascular smooth muscle and on physical exercise-induced thermoregulatory and cardiovascular adjustments in rats. Male Wistar rats were subjected to caudal artery denervation or the sham procedure. Approximately 26-28 days after these procedures, their thermoregulatory and cardiovascular parameters were evaluated at rest and during or following a fatiguing treadmill run. At the end of the experiments, the rats were euthanized, and samples of their tails were removed to evaluate morphometric parameters of the vascular smooth muscle surrounding the caudal artery. Denervated rats showed morphological adaptations, including increased arterial wall thickness and wall-to-lumen ratios. In resting rats and following the fatiguing exercise, caudal artery denervation barely affected the thermoregulatory and cardiovascular parameters evaluated. By contrast, caudal artery denervation attenuated the increase in tail skin temperature, decreased the spontaneous baroreflex sensitivity, and exacerbated the increases in mean arterial pressure in exercising rats. The increased wall-to-lumen ratio of denervated rats correlated negatively with the maximum tail skin temperature attained or cutaneous heat loss sensitivity but correlated positively with the maximum diastolic blood pressure attained during exercise. In conclusion, cutaneous denervation induces vascular remodeling characterized by morphological adaptations of the tail vascular smooth muscle. This vascular remodeling likely underlies the impaired tail heat loss and blood pressure adjustments in denervated rats subjected to physical exercise. Therefore, we have highlighted the importance of cutaneous vascular innervation integrity in thermal and cardiovascular control in stress-challenged rats. In this sense, our findings advance the understanding of thermoregulatory and cardiovascular system reactions after an abrupt and sustained cutaneous vascular innervation injury, which is essential for the treatment of some diseases, such as Parkinson’s disease and type 1 and type 2 diabetes mellitus.